Using Video Physical Asssesment To Enhance Students’ Skills - Ekatrina Wijayanti (Jurnal Keperawatan Respati Yogyakarta, 2018)
Physical assessment is one competency that students must achieve during clinical rotation. Lack of understanding or inability to perform physical examinations will affect achievement data from patients that influences nursing diagnoses. This is challenging for clinical instructors and faculty to assist students to perform well on physical examination. Objective this paper is to preparing student’s nurses able to practice on physical assessment using video. Method this research descriptive quantitative, sample in project was 30 second-year students nurses who enrolled in medical surgical nursing course. Result this research were according to achievement grade among 30 students on practical physical assessment respiratory system there are 26 (86.6%) got A; four students (13.4%) got B, on respiratory examinations. On Practical Physical assessment cardiovascular system the students’ grades are 80% got A, 20% got B. There weren’t students who get C.